Lessons From Health Screening Programs in Asean: A Comparative Policy Analysis Using the National Health Screening Implementation Maturity Index - Kumalasari, Elva; Juwono, Vishnu (International Journal of Social Service and Research, 2025)
Non-communicable diseases (NCDs) account for nearly two-thirds of deaths in Southeast Asia, demanding the strengthening of primary service-based health screening as a key prevention strategy. This study aims to analyze the strategies, patterns, and challenges of national screening programs in ASEAN countries through a comparative policy approach  to strengthen the Free Birthday Health Checkup (PKG) in Indonesia. The research method used a structured narrative review of policy documents, government reports, and academic publications from 11 ASEAN countries, focusing on the dimensions of implementation maturity: geographic scale, universality of age targets, and funding sources. These three dimensions were assessed through a scoring index of 0–3, resulting in a total score out of 9 for mapping the maturity index of national health screening implementation. The results showed significant variations: Indonesia (score 9), Thailand (8), Malaysia, Singapore, and Brunei (7) were in the high index with high coverage and universality; the Philippines (6), Myanmar (5), Cambodia, and Timor-Leste (4) were in the medium index; while Vietnam and Laos (2) remained low, depending on project pilots. In addition, the findings underscore the role of financing stability and digital integration in successful implementation. The implications for Indonesia are that PKG has the potential to serve as a robust health screening model and pilot, but it requires strengthening human resources, standardizing services, and integrating data to overcome regional heterogeneity. Further recommendations include more in-depth research on ASEAN countries for knowledge transfer and capacity building in developing countries.